Chronic scrotal heat stress causes testicular interstitial inflammation and fibrosis: An experimental study in mice - Tung Nguyen-Thanh; Phuoc Dang-Van; Phuc Dang-Ngoc; Won Kim; Tam Le-Minh; Quoc-Huy (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: Chronic heat stress is a risk factor that adversely affects the reproduction system. Inflammation and fibrosis are 2 important response processes to damaged tissues. Objective: This study investigates the association of chronic scrotal heat stress with testicular interstitial inflammation and fibrosis in mice. Materials and Methods: For all experiments, 8-10 wk old male Swiss mice (Mus musculus) (20-23 gr) were divided into 3 groups (n = 10/each). The heat-stress groups were submerged in a water bath at 37 C and 40 C, while the control group was treated at 25 C. The testicular tissues underwent hematoxylin and eosin staining, picro sirius red staining, and immunohistochemistry for intercellular adhesion molecule-1, fibroblast-specific protein 1, F4/80, collagen I, and Ki-67 staining to determine the testicular interstitial inflammation and fibrosis. Results: Chronic scrotal heat stress impairs spermatogenesis and reverses testicular histological structure. In this study, heat stress significantly induced increased interstitial cell proliferation and upregulation of intercellular adhesion molecule-1 expression in the interstitial testicular tissue. In the interstitial testicular tissue, the number of F4/80-positive macrophages and the number of fibroblast-specific protein 1-positive fibroblasts were significantly increased in the heat-exposed groups compared to those in the control group. The heat exposed groups had substantially increased extracellular matrix collagen accumulation in their testicular interstitial tissues. Conclusion: Heat stress adversely affects the testicular structure and spermatogenesis, causes inflammation, and leads to testicular interstitial fibrosis.